Stingless bee honey, the natural wound healer: a review - Abdul Jalil, Mohd Azri; Kasmuri, Abdul Razak; Ab. Hadi, Hazrina (Karger AG, 2017)
Background: The stingless bee is a natural type of bee that exists in almost every continent. The honey produced by this bee has been widely used across time and space. The distinctive feature of this honey is that it is stored naturally in the pot (cerumen), thus contributing to its beneficial properties, especially in the wound healing process. Methods: In this article, several studies on stingless bee honey that pointed out the numerous therapeutic profiles of this honey in terms of its antioxidant, antimicrobial, anti-inflammatory, as well as moisturizing properties are reviewed. All of these therapeutic properties are related to wound healing properties. Results: Antioxidant in stingless bee honey could break the chain of free radicals that cause a detrimental effect to the wounded area. Furthermore, the antimicrobial properties of stingless bee honey could overcome the bacterial contamination and thus improve the healing rate. Moreover, the anti-inflammatory attribute in this honey could protect the tissue from highly toxic inflammatory mediators. The moisturizing properties of the honey could improve wound healing by promoting angiogenesis and oxygen circulation. Conclusion: The application of honey to the wound has been widely used since ancient times. As a result, it is essential to understand the pharmacological mechanism of the honey towards the physiology of the wounded skin in order to optimize the healing rate in the future.